Effects of Medical Material-Based Play Therapy on Pain Levels in Hospitalized Preschool Children Aged 3-6 Years - Pangalila, Milkha; Gannika, Lenny; Simanjuntak, Susi Roida (Inspirasi Foundation, 2024)
Introduction: Pain is a stressor of hospitalization that, if not managed properly, can have physical and psychological impacts on children. One intervention that can be provided to reduce pain in preschool-aged children is play therapy. Objective: This study aims to determine the effect of play therapy using medical materials on the pain levels of hospitalized preschool-aged children. Method: This study uses a pre-experimental design with a one group pretest-posttest design approach. The number of respondents in this study was 25 preschool-aged children who were treated in the Dahlia Pediatric Ward at TK. II R. W. Mongisidi hospital Manado, selected using purposive sampling based on inclusion criteria. Pain measurement was carried out using the Wong Baker FACES Pain Rating Scale. Data analysis was performed using the Nonparametric Wilcoxon test. Results: The Wilcoxon statistical test results showed a p-value of 0.000 (p<0.05), indicating a significant difference in pain levels before and after the play therapy intervention using medical equipment. Conclusion: Based on the analysis, it can be concluded that there is an effect of play therapy using medical materials on the pain levels of hospitalized preschool-aged children. Future researchers interested in this study are encouraged to use a quasi-experimental method with a two-group pretest-posttest design.